1980
DOI: 10.1037/0022-3514.39.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Disparagement humor: Dispositions and resolutions.

Abstract: Sixty-six students rated written jokes on funniness and on eight other scales. Jokes were varied on the equity of retaliation in an exchange of insults, the relative status of the two parties in this exchange, and in another set of jokes, the popularity of a famous victim of the joke squelch. Overretaliation decreased rated funniness and rated resolution ("sensicalness") of the joke. Control for resolution with analysis of covariance reduced the effect of degree of retaliation on funniness to nonsignificance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…For example, the "dispositional theory" of disparagement humor (Zillman & Cantor, 1976) assumes that individuals enjoy a disparaging joke more when they have negative attitudes toward the victimized party (e.g., when the joke belittles a disliked outgroup) and/or positive attitudes toward the agent of disparagement (e.g., when the agent is from the ingroup). Several studies have supported this model (e.g., Cantor & Zillman, 1973;LaFave, Haddad, & Marshall, 1974;Wicker, Baron, & Willis, 1980).…”
Section: Please Scroll Down For Articlementioning
confidence: 87%
“…For example, the "dispositional theory" of disparagement humor (Zillman & Cantor, 1976) assumes that individuals enjoy a disparaging joke more when they have negative attitudes toward the victimized party (e.g., when the joke belittles a disliked outgroup) and/or positive attitudes toward the agent of disparagement (e.g., when the agent is from the ingroup). Several studies have supported this model (e.g., Cantor & Zillman, 1973;LaFave, Haddad, & Marshall, 1974;Wicker, Baron, & Willis, 1980).…”
Section: Please Scroll Down For Articlementioning
confidence: 87%
“…students) preferred jokes that presented the superior as the victim. Similarly, Wicker, Barron, and Willis (1980) found that jokes with a disliked victim were preferred over jokes with a neutral or a liked victim.…”
Section: Group Processes and Intergroup Relationsmentioning
confidence: 93%
“…Wicker, Barron, and Willis (1980) found that a significant effect on funniness occurred in jokes where disliked victims were retaliated against. However, retaliations that occur in natural conversations may not always be very funny (e.g., exchanges that provoke fights).…”
Section: A Puzzling Paradox: What Makes Humor Funny?mentioning
confidence: 97%